The rape of Nanking the forgotten holocaust of World War II - Chang, Iris (Basic Books, 2011)
In December 1937, the Japanese army swept into the ancient city of Nanking. Within weeks, more than 300,000 Chinese civilians and soldiers were systematically raped, tortured, and murdered,a death toll exceeding that of the atomic blasts of Hiroshima and Nagasaki combined. Using extensive interviews with survivors and newly discovered documents, Iris Chang has written the definitive history of this horrifying episode.